Organic‐Inorganic Hybrid Solid Composite Electrolytes for High Energy Density Lithium Batteries: Combining Manufacturability, Conductivity, and Stability - Dries De Sloovere; Jonas Mercken; Jan D'Haen; Elien Derveaux; Peter Adriaensens; Philippe M. Vereecken; Marlies K. Van Bael; An Hardy (Advanced Science)
Abstract The deployment of solid and quasi‐solid electrolytes in lithium metal batteries is envisioned to push their energy densities to even higher levels, in addition to providing enhanced safety. This article discusses a set of hybrid solid composite electrolytes which combine functional properties with electrode compatibility and manufacturability. Their anodic stability >5 V versus Li+/Li and compatibility with lithium metal stem from the incorporated ionic liquid electrolyte, whereas the organic‐inorganic hybrid host structure boosts their conductivity up to 2.7 mS cm−1 at room temperature. The absence of strong acids enables compatibility with porous NMC811 electrodes. Liquid precursor solutions can be readily impregnated into porous electrodes, facilitating cell assembly. Electrolytes containing TFSI− as the only anion have a superior compatibility toward high‐voltage positive electrode materials, whereas electrolytes containing both FSI− and TFSI− have a better compatibility toward lithium metal. Using the former as catholyte and the latter as anolyte, NMC811/Li coin cells retain up to 100% of their initial capacity after 100 cycles (0.2 C, 3.0–4.4 V vs Li+/Li). Because of their unprecedented combination of functional properties, electrode compatibility, and manufacturability, these hybrid solid composite electrolytes are potential candidates for the further development of lithium metal battery technology.